Poly-Systemic Analysis of Military Students’ Discipline - L. Ya. Dorfman; A. V. Dubrovsky; A. P. Andrunik; E. A. Tsariev; V. N. Lyadov (Образование и наука)
Introduction. The concept of “discipline” has not been thoroughly investigated in psychology yet. In addition, a system of military higher education needs for new psychological knowledge on discipline structure and its formation.The aim of the research was to reveal poly-systemic characteristics of selfdiscipline concerning its psychological components and interrelations between them.Methodology and research methods. The research was based on the polysystemic approach and the theory of “meta-individual world”, which establishes a heterogeneous nature of an individual. The questionnaire on discipline was the main diagnostic tool, which was approved to be reliable and valid. Confirmatory factor and comparative analysis were used to process the results obtained.Results and scientific novelty. For the first time, the poly-system origin of discipline has been revealed theoretically, logically and empirically. Its composition and changing structures according to a poly-system criterion were described. The structure of discipline included the following indicators: “obedience from childhood”, “self-restraint”, “social motives”, “orientation to result”, “acceptance of self-responsibility” and “consciousness”. According to internal and external factors, which have an impact on discipline, its systems were distinguished as follows: social discipline, self-discipline and shared discipline. Three models were tested: a unitary model (without allocation of discipline systems), a dual parallel model (with independent systems of social discipline and self-discipline) and a dual overlapping model (composite). Compared to the other two models, the advantage of composite model was justified. However, one-factor, twofactor and three-factor analysis showed that each of models has its advantages and significance. It was shown that components (indicators) of discipline were redistributed variously in different models. The obtained results were explained by the integrative effects, which are similar to a structural isomerism: the same components of discipline can be the part of several systems. On this basis, the authors proposed the idea that latent factors switch discipline components from one system to the other.Practical significance. The materials of the present publication have practical value for the specific ways to form and strengthen the discipline of military students. To develop this important capacity within military personnel in the educational process, it is necessary to use external and internal resources in combination (i.e. components of social discipline and self-discipline). To provide more effective assessment of students’ professional suitability, it is recommended to pay attention to discipline diagnostics in the process of selection of entrants for admission to military educational institutions, and in particular, to determine the expressiveness of indicators of self-restraint and obedience from childhood.